Environmental applications of geochemical modeling - Zhu, Chen (Cambridge Univ. Press, 2002)
This book discusses the application of geochemical models to environmental practice and studies, through the use of numerous case studies of real-world environmental problems, such as acid mine drainage, pit lake chemistry, nuclear waste disposal, and landfill leachates. In each example the authors clearly define the environmental threat in question; explain how geochemical modeling may help solve the problem posed; and advise the reader how to prepare input files for geochemical modeling codes and interpret the results in terms of meeting regulatory requirements.